Interplay of trauma-triggered auto-inflammation and T-cell auto-reactivity in posttraumatic dystrophy - Scola, Egmont (Frontiers in Immunology, 2025)
Damage-associated molecular patterns (DAMPs) cause sterile auto- inflammation after a traumatic incident in human tissues via innate immunity. The auto-reactivity of natural killer T cells (NK-T cells) instigated by DAMP-activated exocytosis of dendritic cell (DC) vesicles forces implementation of T helper cells, which aggravate inflammatory reactions such as AV shunts and hyperperfusion of the ROI with hypoxia of capillaries. For example, in trauma patients, elevated venous pO2 was found compared to that in the contralateral extremity of > 20 mmHg 2.66 kPa. Scintigraphic perfusion of the ROI showed elevated values of over 90% on average compared with the healthy side. These findings suggest local capillary stasis, hypoxia, and acidosis. In the initial process, macrophages and dendritic cells play an important role, along with DAMPs, in the activation of innate immunity. Additional tissue-homing NKT cells are activated by releasing pro-inflammatory cytokines. The resulting “cytokine storm” opens options for perpetuation by diverse autocrine loops and inflammasomes. Finally, antibodies against self-molecules are directed against cells and tissues. In a biological sense, this represents the worst scenario in chronic-aseptic inflammatory reactions after trauma and must be fought from the beginning to avoid chronification and spreading, which can lead to fibrosis and functional impairment of the injured extremity. This is the feared endpoint of posttraumatic dystrophy.